Tantangan Manajemen Waktu Pada Mahasiswa Paruh Waktu Dalam Memenuhi Prestasi Akademik - M.Krisna Bagus Virgiana; Angky Melani; Dewi Khurun Aini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research explores the time management challenges of part-time students in meeting academic achievements. This research uses a qualitative method with an in-depth interview approach. The population in this study were students who were working or had previously worked. The results of this research identify the factors that motivate students to work part-time, including financial need, career path, study alignment, accessibility, and desire to gain experience. Although there are students who prioritize academics above their work, others view both responsibilities as equally important. These findings highlight the challenges part-time students face in managing work schedules, academic commitments, and personal well-being.